2016
DOI: 10.1097/rli.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal Blood Volume Assessed by C-Arm–Based Computed Tomography in Immediate Posttreatment Evaluation of Drug-Eluting Bead Transarterial Chemoembolization in Hepatocellular Carcinoma

Abstract: Parenchymal blood volume values as derived from C-arm CT acquisitions in combination with nonenhanced and contrast-enhanced C-arm CT images are useful in posttreatment assessment of DEB-TACE in HCC. Residual tumor perfusion in PBV maps have predictive potential for mid-term tumor response in HCC and could allow a more individualized treatment schedule for DEB-TACE in HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
(28 reference statements)
3
26
0
Order By: Relevance
“…Regarding perfusion parameters acquired by VPCT before and after TACE, our results yielded comparable results to previous studies evaluating TACE in HCC [ 16 , 18 ]. The same applies when comparing results of PBV measurement in HCC lesions and healthy liver parenchyma of our study to previous published data [ 10 , 13 ]. Comparing perfusion parameters acquired by VPCT and those assessed by C-arm CT (PBV) revealed some interesting additional information provided by C-arm CT, indicating an adaptation in tumor and healthy liver parenchyma to treatment.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Regarding perfusion parameters acquired by VPCT before and after TACE, our results yielded comparable results to previous studies evaluating TACE in HCC [ 16 , 18 ]. The same applies when comparing results of PBV measurement in HCC lesions and healthy liver parenchyma of our study to previous published data [ 10 , 13 ]. Comparing perfusion parameters acquired by VPCT and those assessed by C-arm CT (PBV) revealed some interesting additional information provided by C-arm CT, indicating an adaptation in tumor and healthy liver parenchyma to treatment.…”
Section: Discussionsupporting
confidence: 72%
“…A similar finding has recently been published concerning the assessment of PBV maps. Areas of residual increased PBV seem to be associated with an unfavorable outcome in mid-term tumor response [ 13 ]. We therefore concluded that absolute perfusion values before and after treatment might not be ideal predictors for treatment response, but ratios of perfusion parameters before and after DEB-TACE should be more appropriate for the assessment of treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Shortly after this, further studies suggested baseline pre-intervention cerebral blood volume as a predictor of outcomes in patients undergoing intra-arterial stroke therapies, [ 6 ] and that this technique may substitute for multisection CT imaging to some extent in selected patients with acute stroke for the sake of saving time. [ 7 ] Apart from brain, new studies demonstrate that FD-PBV technique is useful in post-treatment assessment of transarterial chemoembolization in hepatocellular carcinoma with predictive potentials in prognosis [ 8 ] and detecting early functional response to transpulmonary chemoembolization. [ 9 ] Our preliminary data show that it could provide quantitatively assessment toward hemodynamic changes of kidney blood perfusion before and after endovascular treatment for RAS.…”
Section: Discussionmentioning
confidence: 99%
“…C-arm CT consisted of unenhanced rotation (mask run) and contrast enhanced rotations (return and fill run) for acquisition of parenchymal blood volume (PBV) maps (time per rotation 4 s, total examination time 16 s, 90 kV, 200 • total angle, 0.8 • per frame, 248 frames, matrix 616 × 480 pixel, flat panel size 616 m, dose 0.36 Gy per frame) [7,8]. Dose area products (DAP) were documented for each C-arm CT.…”
Section: C-arm Ct and Post-processingmentioning
confidence: 99%